1985
DOI: 10.1161/01.cir.72.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of vascular hydraulic load in patients with heart failure.

Abstract: Aortic input impedance and hydraulic power were derived from simultaneous catheter recordings of ascending aortic pressure and velocity in eight normal subjects and 11 age-matched subjects with clinical heart failure secondary to idiopathic congestive cardiomyopathy. Resting data revealed the characteristic depression of cardiac output and elevation of systemic vascular resistance in patients with heart failure. The pulsatile component of vascular hydraulic load, characteristic impedance (Zc), was similar in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 47 publications
4
42
1
Order By: Relevance
“…The values reported from our laboratory are in accord with those from previous studies in both normal subjects and patients with heart failure but are at variance with others. 12 The precise identification of the first minimum in the continuous input impedance spectrum is precluded by the constraints of our method, since the harmonics derived are integral multiples of the fundamental frequency. It is unlikely that the true fmin exactly coincides with the fmin used in this study; therefore, changes in this variable may not truly reflect a shift in the actual minimum of the spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values reported from our laboratory are in accord with those from previous studies in both normal subjects and patients with heart failure but are at variance with others. 12 The precise identification of the first minimum in the continuous input impedance spectrum is precluded by the constraints of our method, since the harmonics derived are integral multiples of the fundamental frequency. It is unlikely that the true fmin exactly coincides with the fmin used in this study; therefore, changes in this variable may not truly reflect a shift in the actual minimum of the spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven of these patients have been previously described. 12 Eleven subjects (10 men, one woman), 22 to 65 years old (mean 43 ± 14) were referred for diagnostic cardiac catheterization and coronary angiography because of chest pain syndromes. All had structurally normal coronary arteries, normal cardiac output, and normal angiographic left ventricular ejection fraction (range 56% to 79%, mean 70 + 8%).…”
Section: Methodsmentioning
confidence: 99%
“…Aerobic exercise is normally associated with a decrease in SVR; an increase in heart rate, stroke volume, cardiac output, and mean arterial pressure; decreased reflection magnitude with earlier arrival of the reflected wave; and decreased pressure augmentation from wave reflections, without changes in Zc. 14,15 In contrast, isometric exercise is associated with an increased heart rate, unchanged or decreased stroke volume with no or little increase in cardiac output, increased SVR, increased mean arterial pressure, increased reflection magnitude with earlier wave reflections, increased Zc, and a marked decreased in TAC 16 ; changes in pulsatile hemodynamics during isometric exercise are not apparent from pulse pressure measurements. Although these are average responses, great interindividual variability in these responses exists.…”
Section: Resting Versus Provoked Loadmentioning
confidence: 95%
“…19,20 This notion is in keeping with our findings, where reflected wave components in the aorta seemed relatively unaffected by exercise-induced peripheral vasodilation, despite large increases in the magnitude of the incident pressure wave. Interestingly, Laskey et al 24 also found a reduction in the first harmonic of the reflection coefficient (suggesting diminished reflected wave magnitude) on initiation of exercise in healthy subjects. Adding to this observation, this current study found a strong and negative association between the change in magnitude of reflection and change in central systolic BP with exercise.…”
Section: Exercise Hemodynamics: Forward and Reflected Waves In The Aortamentioning
confidence: 97%